Legal Paradigms in Addressing Social Polarization on Social Media - Yusup, Aldian (Journal of Law and Humanity Studies, 2024)
This research aims to explore the legal paradigm in overcoming social polarization that is increasingly sharp on social media. This polarization is exacerbated by digital platform algorithms that reinforce "echo chambers" and the spread of certain interest-based content, including disinformation and hate speech. This phenomenon triggers ideological segregation and social conflicts that threaten the stability of society and democracy. The study uses a qualitative method with a literature study approach, analyzing journal articles, books, and policy documents from the last five years (2018–2023) that are relevant to law and social media. The data collection technique is carried out through a systematic document review, while data analysis uses a thematic approach to map the main patterns and concepts related to legal regulations and digital platforms. The findings of the study show that an adaptive and inclusivity-based legal paradigm is needed to overcome the challenges of social polarization. Regulations should include algorithmic transparency, content moderation, and human rights protections without sacrificing freedom of speech. In addition, collaboration between the government, social media platforms, and the public is needed to create a healthy digital space. This research makes a significant contribution to the development of legal and technological literature and offers policy recommendations that can be applied practically to reduce the impact of social polarization in the digital era.